a. Yes, we can combine the like terms to simplify the equation. 2x + 3 + x - 6 can be simplified to 3x - 3.
b. To solve for the value of x, we can substitute 3x - 3 into the equation and solve for x.
3x - 3 = 180
To find the value of x, we can add 3 to both sides of the equation:
3x - 3 + 3 = 180 + 3
This simplifies to:
3x = 183
Finally, we can divide both sides of the equation by 3 to solve for x:
3x/3 = 183/3
x = 61
Therefore, the value of x is 61.
c. Now that we have the value of x as 61, we can substitute that value into the angle (2x + 3) and (x - 6).
For (2x + 3):
(2(61) + 3)
= 122 + 3
= 125
For (x - 6):
(61 - 6)
= 55
Therefore, when we fill in x = 61 into (2x + 3), we get 125, and when we fill in x = 61 into (x - 6), we get 55.
A. Supplementary angles total up to 180o. You should use this information to write the equation: 2x + 3 + x - 6 = 180. Can you combine the like terms to simplify the equation?
b. Use the equation from Part A to solve for the value of x.
c. Now, use the value of x from Part B to fill into the angle (2x + 3) and what do you get? What about when you fill x into the other angle (x - 6)?
3 answers
To solve for the value of x, we can substitute 3x - 3 into the equation and solve for x.
3x - 3 = 180
To find the value of x, we can add 3 to both sides of the equation:
3x - 3 + 3 = 180 + 3
This simplifies to:
3x = 183
Finally, we can divide both sides of the equation by 3 to solve for x:
3x/3 = 183/3
x = 61
Therefore, the value of x is 61.
c. Now that we have the value of x as 61, we can substitute that value into the angle (2x + 3) and (x - 6).
For (2x + 3):
(2(61) + 3)
= 122 + 3
= 125
For (x - 6):
(61 - 6)
= 55
Therefore, when we fill in x = 61 into (2x + 3), we get 125, and when we fill in x = 61 into (x - 6), we get 55. is this correct?
3x - 3 = 180
To find the value of x, we can add 3 to both sides of the equation:
3x - 3 + 3 = 180 + 3
This simplifies to:
3x = 183
Finally, we can divide both sides of the equation by 3 to solve for x:
3x/3 = 183/3
x = 61
Therefore, the value of x is 61.
c. Now that we have the value of x as 61, we can substitute that value into the angle (2x + 3) and (x - 6).
For (2x + 3):
(2(61) + 3)
= 122 + 3
= 125
For (x - 6):
(61 - 6)
= 55
Therefore, when we fill in x = 61 into (2x + 3), we get 125, and when we fill in x = 61 into (x - 6), we get 55. is this correct?
Yes, that is correct. Based on the value of x as 61, when you substitute it into the angle (2x + 3), you get 125, and when you substitute it into the angle (x - 6), you get 55.